Implementation of Substantive Justice in Juvenile Serious Crime Cases in Indonesia - Made Sinthia Sukmayanti; AAA. Ngurah Tini Rusmini Gorda (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
Legal protection for children in conflict with the law constitutes an essential component of the state's responsibility to ensure the fulfillment of children's fundamental rights as a vulnerable group within society. Nevertheless, the increasing involvement of children in serious crimes indicates that the juvenile criminal justice system in Indonesia continues to face significant challenges in achieving substantive justice. This study aims to analyze the implementation of substantive justice in addressing juvenile offenders involved in serious crimes and to formulate an ideal juvenile criminal justice model grounded in the principles of justice. The research employs a socio-legal method with statutory and conceptual approaches. The findings reveal that the implementation of substantive justice has not yet been fully optimized due to several factors, including normative disharmony between child protection principles and the limitations imposed on diversion within the Juvenile Criminal Justice System Law, the predominance of a retributive approach, inconsistencies in judicial decisions, and the inadequacy of rehabilitation facilities. Accordingly, a reconstruction of the juvenile criminal justice system is required through a collaborative restorative model that places rehabilitation, social reintegration, the protection of children's rights, victim recovery, and societal interests in a balanced framework as its primary orientation.